Integration of enabling methods for the automated flow preparation of piperazine-2-carboxamide - Ingham, Richard J.; Battilocchio, Claudio; Hawkins, Joel M.; Ley, Steven V. (Beilstein Journal of Organic Chemistry, 2014)
Here we describe the use of a new open-source software package and a Raspberry Pi® computer for the simultaneous control of multiple flow chemistry devices and its application to a machine-assisted, multi-step flow preparation of pyrazine-2-carboxamide – a component of Rifater®, used in the treatment of tuberculosis – and its reduced derivative piperazine-2-carboxamide.
Keywords: automation; flow chemistry; hydration; hydrogenation; sustainable processing